FORENSIC PSYCHOLOGY AND NEUROPSYCHOLOGY FOR CRIMINAL AND CIVIL CASES - Hall, Harold V.; Poirier, Joseph G. ([S.l.] : CRC PRESS, 2022)
Today's increasingly sophisticated psychological and neuropsychological assessments allow for a greater understanding, and improved evaluations, in forensic psychology. By integrating discussions of modern psychological and neuropsychological tests, with extant civil and criminal cases, Forensic Psychology and Neuropsychology for Criminal and Civil Cases, Second Edition serves as a fully-updated, professional resource outlining modern behavioral science's impact on the legal system. This second edition synthesizes the theoretical, empirical, and clinical literature, examining it through the lens of case application. The book is divided into three parts to look at foundational legal, ethical and applied issues; criminal forensic evaluations; and civil forensic evaluations. Chapters new to this edition address substance abuse and intoxication, interviewing and interrogation, criminal profiling, faked amnesia and recall skills, post-concussive syndrome (PCS), post-traumatic stress disorder (PTSD), and trends and research directions. Clinicians, researchers and psychologists practicing in any number of related fields will be able to address relevant questions from both criminal-forensic and civil-forensic perspectives. Key features: Presents the latest advances in methodology and technology to assist forensic professional in assessment and case formulation in the search for ground truth in applied settings Outlines base rates for forensic areas of concern, especially helpful in evaluation, report writing and courtroom testimony as an expert witness Addresses complex criminal issues such as competency to stand trial, criminal responsibility, mitigating defenses, and violence risk Forensic Psychology and Neuropsychology for Criminal and Civil Cases, Second Edition is an invaluable resource to clinicians, experts witnesses, and legal professionals--a helpful adjunct for mental health experts to formulate sound direct and cross-examination strategies, and eliciting suggestions for forensically-related treatment and intervention.
Keywords: Forensic psychology; Forensic neuropsychology; Violence -- Psychological aspects; PSYCHOLOGY / General; LAW / Medical Law & Legislation; MEDICAL / Neuroscience